UTILIZATION OF INSTRUCTIONAL MEDIA AND QUALITY OF LEARNING OUTCOMES IN ENGLISH LANGUAGE IN PUBLIC SECONDARY SCHOOLS IN MBOONI EAST SUB-COUNTY, KENYA - MUSAU, ROSALIA MINOO (MksU Press, 2023)
In Kenya, the teaching of English language in public secondary schools is a matter of concern. The performance of English language in examinations has been below average nationally. This has prompted the researcher to investigate how the utilization of instructional media in the teaching of English language impacts on learning outcomes in public secondary schools in Mbooni East Sub-County, Kenya. The guiding objectives were; to establish teacher preparedness in the use of instructional media and quality of learning outcomes in teaching of English language in public secondary schools in Mbooni East Sub-county; to identify the types of instructional media used in teaching of English language and quality of learning outcomes in public secondary schools in Mbooni East Sub-county; to establish teachers workload and quality of learning outcomes in teaching of English language in public secondary schools in Mbooni East Sub-county and to assess media use and quality of learning outcomes in the teaching of English language in public secondary schools in Mbooni East SubCounty. The study adopted Multimedia learning theory by Richard Mayer. The study used descriptive survey research design. The target population was 49 public secondary schools, 49 Heads of Languages Department, 111 teachers of English and 3120 form three students. The researcher used stratified random sampling technique to sample one extra county school, three county schools and eight sub-county schools giving a total of 12 schools. Purposive sampling was used to select 12 Heads of Languages Department from the 12 sampled schools. Simple random sampling was used to select one form three stream in schools that have more than one stream. In addition, the study adopted simple random sampling to select 26 students from each of the 12 sampled form three streams giving a total of 312 form three students. The teacher of English who teaches the sampled stream was purposively sampled in each school and thus, giving a sample of 12 teachers. Questionnaires were used as research instrument for teachers of English and a written English test for the students. Interview schedules were applied to the Heads of the Languages Department. The piloting of instruments was conducted in one school from the Makueni Sub-County to ascertain the reliability of the instruments. The instruments’ validity was determined through expert opinion from the school of Education of Machakos University. Quantitative data was analyzed through descriptive statistics and presented in frequencies, means and percentages with the aid of Statistical Package for Social Sciences (SPSS) version 21. Content analysis was used to analyze qualitative data which was thematically presented in prose. Findings show that teachers of English in public secondary schools in Mbooni East subcounty are ill prepared concerning the use of instructional media. In addition, quality of learning outcomes in English language in the sub-county is slightly below average, sub-county schools perform poorer and female students outshine their male counterparts. It was concluded that instructional media enhance learning outcomes in English language, teacher’s workload influences use of instructional media. The study recommends that the Ministry of Education should equip public schools with instructional resources, train teachers on the modern teaching methodologies and employ more teachers to reduce their workload. In addition, school principals and Quality Assurance and Standards Officers should emphasize to teachers to use instructional media in teaching English language.